Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1975
DOI: 10.1172/jci108098
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the elevated extracellular concentration of cyclic AMP in uremic man.

Abstract: A B S T R A C T This study was designed to elucidate the mechanism of elevation of plasma cyclic AMP in uremic man. Plasma cyclic AMP was measured in 15 normal subjects and in 18 patients with severe renal failure. In some members from both groups the kinetic parameters of the metabolism of extracellular cyclic AMP were measured.Plasma cyclic AMP was elevated from 23 nM in control subjects to 59 nM in uremic patients, regardless of the presence or absence of the kidneys or parathyroid glands. A single pass of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The capture step avoids possible false positives from naturally occurring cAMP in a sample. This is even more relevant because cAMP has been found to be abnormally elevated in certain stages of pregnancy [28], hyperthyroidism [29], renal failure [30,31], and eczema [32] among others. For methods with potential clinical application, the specificity for the source of cAMP is essential.…”
Section: Discussionmentioning
confidence: 99%
“…The capture step avoids possible false positives from naturally occurring cAMP in a sample. This is even more relevant because cAMP has been found to be abnormally elevated in certain stages of pregnancy [28], hyperthyroidism [29], renal failure [30,31], and eczema [32] among others. For methods with potential clinical application, the specificity for the source of cAMP is essential.…”
Section: Discussionmentioning
confidence: 99%
“…HD can reduce the level of mid dle molecules with improvement in lympho cyte function [30]. A long list of factors capa ble of interfering with lymphocyte function include: nutritional status [70], plasma cyclic AMP levels [71], thymosin deficiency [72], a reversible vitamin B6 coenzyme deficiency [73] and a variety of circulatory cytotoxic antibodies [74], Thus, it is not surprising that several studies have found the suppressive effect nondialyzable [54,[56][57][58] and others have found improvement after dialysis [54][55][56],…”
Section: Altered In Vitro Lymphocyte Functionmentioning
confidence: 99%
“…Occupancy of the thrombocyte alpha-2-adrenoccptor leads to an inhibition of adenylate cyclase activity [for review see 17], mediated by an inhibi tory G protein [for review see 7] and causes or facilitates platelet aggregation [4,17], Stimulation of adenylate cyclase activity, leading to elevated cAMP levels, reverses the thrombin-induced increases in thrombocytefree calcium concentrations and exerts thus an antiaggregatory response [21]. A dimin ished platelet adhesiveness, which seems to be closely linked to serum urea nitrogen lev els, is believed to be a cause of uremic bleed ing disorders [6], Additionally, an increase in plasma and thrombocyte cAMP content and of thrombocyte adenylate cyclase activ ity has been observed in uremia [8,19], A possible explanation for this alteration was presented by Brodde et al [1,2], who found a diminished number of thrombocyte alpha-2-adrenoceptors and a shift of the doseresponse curve of (-)-adrenaline, inhibiting adenylate cyclase activity, towards higher concentrations. It was speculated that the decrease in the alpha-2-adrenoceptor num ber was due to elevated catecholamine lev els, possibly because of an impaired neu ronal uptake mechanism in uremia [9], How ever, arguments against a pathophysiological relevance of these findings are furnished by studies of MacFarlane and Stump [12], showing that only about 50% of the throm bocyte alpha-2-adrenoceptors have to be oc cupied to reach maximal inhibition of ade nylate cyclase activity, whereas the decrease in receptor number, observed by Brodde et al [1,2], was only about 20%.…”
Section: Discussionmentioning
confidence: 99%